The Use of Microcontrollers in Air Quality Monitoring: A Systematic Literature Review - Sabado, Wilber B. (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose  – this paper aimed at identifying the low-cost technologies using microcontrollers like Arduino and Raspberry Pi used in air quality monitoring in the Philippines for 2023. Method  – This paper utilized a systematic literature review that employed strategies in selecting, analyzing, evaluating, and summarizing papers from a database of documents. Similarly, inclusion/exclusion criteria were set. Results  – Using the web address of Google Scholar which is scholar.google.com, a search result for the keywords “microcontrollers arduino raspberry pi air quality monitoring Philippines” returned 109 results. Conclusion  – Air quality monitoring can be done using a low-cost microcontroller like Arduino or Raspberry Pi. An effective solution for pollution monitoring using a wireless sensor network to provide real time pollution data. Recommendations  – To encourage developers to develop an air quality monitoring system using Arduino or Raspberry Pi microcontrollers with integrated sensors. Research Implications  – This research seeks to identify the current air quality monitoring systems for 2023 using Arduino or Raspberry Pi microcontrollers. Practical Implications  – This research proves that technology offers cheaper alternatives in the development of air quality monitoring systems. Social Implications  – This research shows opportunities for students to use technology.